Deformation of phospholipid vesicles in an optical stretcher1. Issue 30 (14th August 2015) - Delabre, Ulysse; Feld, Kasper; Crespo, Eleonore; Whyte, Graeme; Sykes, Cecile; Seifert, Udo; Guck, Jochen
<x xml:space="preserve">Abstract</x> Deformation of a vesicle in a dual wavelength optical stretcher that enables to stretch and heat the vesicle below and above the transition temperature.